THE ROLE OF ASSISTANT GENERAL TO SUPPORT AND STRENGTHEN BATTLE OPERATIONS OF INFANTRY BRIGADE UNITS - Darmawan, Darmawan; Sudaryati, Sudaryati (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
ABSTRACT - This conceptual paper proposes a model theory of applying strategic management to the field of personnel resource management. When a country is about to engage in war, one very important thing to understand is the characteristic of the war. In peacetime, the armed forces must prepare for wartime. No two wars are identical, because war is produced by The Paradoxical Trinity. Therefore, the big question is: what is the function and role of Adjutant General corps in this increasingly multidimensional war? The recruitment of adjutant general personnel can no longer rely solely on officers and staff and civil servants on the basis of qualifications as drafted in the Conception of the Adjutant General Transformation in order to support the basic tasks and functions of Army. The Adjutant General corps will also need officers and staff who have experience in the war and staff who have comprehensive analysis skill that includes the three elements of war in The Paradoxical Trinity. This means that Adjutant General should have a specialty in accurately analysing personnel’s capabilities. The main advantage of this scheme is allowing higher vigilance to anticipate war. The ability to receive data and then process it will affect the strength of the army as a whole. Upon this conclusion it is recommended to establish a new sub directorate which functions are to collect information on legislation, daily orders; organizing, inspecting, controlling, and mobilizing troops, military punishment, desertions and rotation of troops to then analyse it for the purpose of providing reports and suggestions for personnel/troop deployment, logistics and movements at headquarters and users. The breadth of this function will result in the importance of the improvement of the competence and position of the Directorate of Adjutant General from Brigadier General to Major General.